Affect-Based Problem Drinking Risk: The Reciprocal Relationship between Affective Lability and Problem Drinking. (5th April 2021) - Peterson, Sarah J; Atkinson, Emily A; Riley, Elizabeth N; Davis, Heather A; Smith, Gregory T
Abstract: Aims: Negative affect has been implicated in risk for the development of problematic drinking behavior. Furthermore, there is evidence for reciprocal relationships between negative affect and problem drinking, such that engagement in problem drinking also predicts increases in negative affect. However, affective models of risk often fail to consider affective lability—the experience of rapidly changing mood. Although affective lability appears to increase risk for problem drinking, it is unknown if this relationship persists above and beyond other affect-related constructs (e.g. depression, anxiety) and if it is reciprocal in nature. Accordingly, we used a longitudinal survey design to examine (a) if affective lability predicts problem drinking above and beyond depression and anxiety and (b) if affective lability and problem drinking demonstrate a reciprocal relationship. Methods: First-year college students ( n = 358) participated in a three wave longitudinal study. We constructed a structural equation model (SEM) of a random intercept cross-lagged panel model to test our hypotheses. Results: Consistent with our hypotheses, affective lability predicted increases in problem drinking while anxiety and depression did not. Problem drinking and affective lability demonstrated a reciprocal relationship in which increases in one predicted increases in the other at subsequent time points. This relationship was present beyond the predictive effects of anxiety or depression. Conclusions: Affective lability appears to be an important affect-based predictor of problem drinking, and there may be a reciprocal, risk-enhancing relationship between affective lability and problem drinking. Components of negative affect, such as depression or anxiety, have been shown to predict risk for problem drinking, and vice versa. A less considered construct, affective lability, predicted problem drinking while anxiety and depression did not add any predictive power. Problem drinking and affective lability also appeared to demonstrate a reciprocal relationship.